Long-term benefit from immune modulation and anti-inflammatory treatment in metastatic mesothelioma. (2020) - Dalgleish, Angus G.; McLean, Emma; Patel, Nirav; Rahman, Najib
Abstract: A 64 year old male heating engineer was investigated for a persistent cough and found to have epithelioid mesothelioma with pleural effusion, lung nodules and increased thoracic lymph nodes. He declined standard of care treatment following his own research and he was enrolled in a named patient programme of IMM-101. He was advised to correct his low vitamin D3 level and to start using anti-inflammatories such as aspirin, bromelain and low dose Naltrexone. At review one year later a CT scan showed no change and he continued on the regimen. Four years after the diagnosis a CT scan showed that there was a modest but definite progression of the left malignant pleural thickening, and a new right-sided effusion, enlargement of several intrathoracic nodes which had been noted on the early scans. The chest wall lump eventually broke down and required local radiotherapy. He then developed abdominal pain and found to have peritoneal disease. Last year he obtained the cannabinoids CBD and THC which slowed down the disease and a CT scan after he had been on this for six months, showed that his disease was fairly stable with marginal progression.